Anisotropic deformation of extruded magnesium alloy AZ31 under uniaxial compression: A study with simultaneous in situ synchrotron x-ray imaging and diffraction. (November 2016) - Lu, L.; Huang, J.W.; Fan, D.; Bie, B.X.; Sun, T.; Fezzaa, K.; Gong, X.L.; Luo, S.N.
Abstract: In situ synchrotron x-ray imaging and diffraction are used to investigate anisotropic deformation of an extruded magnesium alloy AZ31 under uniaxial compression along two different directions, with the loading axis (LA) either parallel or perpendicular to the extrusion direction (ED), referred to as LA ∥ ED and LA ⊥ ED, respectively. Multiscale measurements including stress–strain curves (macroscale), x-ray digital image correlation (mesoscale), and diffraction (microscale) are obtained simultaneously. Electron backscatter diffraction is performed on samples collected at various strains to characterize deformation twins. The rapid increase in strain hardening rate for the LA ∥ ED loading is attributed to marked 10 1 ¯ 2 extension twinning and subsequent homogenization of deformation, while dislocation motion leads to inhomogeneous deformation and a decrease in strain hardening rate. Graphical abstract: